Commemorative Program 2013 (Symphony in the Flint Hills, 2013)
The schedule of activities and program, a message from the Commanding General of Fort Riley, information about the Kansas City Symphony, conductor Aram Demirjian, and others. The program also recognizes sponsors, patrons, and volunteers.
Keywords: Program notes; Prairie; Aram Demirjian; Kansas City Symphony